A reliable Pd-mediated hydrogenolytic deprotection of BOM group of uridine ureido nitrogen - Aleiwi, Bilal A. (2012)
The benzyloxymethyl (BOM) group has been utilized widely in syntheses of a variety of natural and non-natural products. The BOM group is also one of few choices to protect uridine ureido nitrongen. However, hydrogenolytic cleavage of the BOM group of uridine derivatives has been unrealizably performed via heterogeneous conditions using Pd catalysts. One of the undesirable by-products formed by Pd-mediated hydrogenation conditions is the over-reduced product of which the C5–C6 double bond of the uracil moiety was saturated. To date, we have generated a wide range of uridine-containing antibacterial agents, where the BOM group has been utilized in their syntheses. In screening of deprotection conditions of the BOM group of uridine ureido nitrogen under Pd-mediated hydrogenation conditions, we realized that the addition of water to the (i)PrOH-based hydrogenation conditions can suppress the formation of over-reduced uridine derivatives and the addition of HCO(2)H (0.5%) dramatically improve the reaction rate. An optimized hydrogenation condition described here can be applicable to the BOM-deprotections of a wide range of uridine derivatives.